Sex assessment efficacy of permanent maxillary first molar cusp dimensions in Indians - Achla Bharti Yadav; Punnya V Angadi; Sumit Kumar Yadav (Wolters Kluwer Medknow Publications, 2015)
Background: The human first maxillary molar provides clues about evolution and is functionally important. It has four main cusps, and each cusp has an independent growth pattern and different evolutionary background. Though less explored, the analysis based on measurement of each cusp appears to be more meaningful biologically than conventional measurements of the whole crown. Aim: This study aimed to demonstrate the extent of sexual dimorphism in permanent maxillary first molar cusp diameters and their potential utility in sex prediction among Indians using logistic regression analysis (LRA). Materials and Methods: The mesiodistal and buccolingual (BL) crown diameters along with cusp dimensions and cusp indices of right maxillary first molar were measured in an Indian sample (149 males, 151 females; age range of 18-30 years). The possible sex dimorphism in these parameters was evaluated, and LRA was performed to ascertain their usefulness in sex prediction. Results: BL crown dimension and the hypocone (distolingual) cusp showed the highest sexual dimorphism. The combination of metacone and hypocone, i.e., distal cusp diameters among cusp parameters showed the highest accuracy (61.3%). While, on combining all the crown and cusp diameters together the overall accuracy was raised (64.3%). Conclusion: This study supports the ontogeny hypothesis suggesting that early-forming mesial cusps demonstrate less sexual variation as compared to subsequently formed distal cusps in the maxillary molar. Though the sex identification accuracy for cusp diameters of the permanent maxillary first molar in Indians is relatively moderate (≈61%), it can be used as an adjunct for sexing of adult Indians in forensic contexts.